The burning chambers - Mosse, Kate, 1961- (Mosse, Kate, 1961- Burning chambers series., 2019)
"Circe France, 1562: Nineteen-year-old Minou Joubert receives an anonymous letter at her father's bookshop. Sealed with a distinctive family crest, it contains just five words: SHE KNOWS THAT YOU LIVE. But before Minou can decipher the mysterious message, a chance encounter with a young Huguenot convert, Piet Reydon, changes her destiny forever. For Piet has a dangerous mission of his own, and he will need Minou's help if he is to stay alive."--